Controlling Regiochemistry in the Syntheses of Boraindanes from Diborane(4) Starting Materials. Issue 32 (7th July 2016) - Arnold, Nicole; Braunschweig, Holger; Ewing, William C.; Kupfer, Thomas; Radacki, Krzysztof; Thiess, Torsten; Trumpp, Alexandra
Abstract: The reaction of tert ‐butylisonitrile ( t BuNC) with 1, 2‐dihalo‐1, 2‐diduryldiborane leads initially to the formation of the mono‐base adduct of the symmetrical diborane(4), which then undergoes an intramolecular cyclization resulting in the formation of a 1‐boraindane. This result is in contrast to a previously reported cyclization of a mono‐isonitrile adduct of an unsymmetrical 1, 1‐pinacol‐2, 2‐diaryldiborane(4), which results in the formation of a 1‐boraindane. This latter result is herein confirmed by the reaction of 1, 1‐difluoro‐2, 2‐dimesityldiborane(4) with t BuNC, which yielded the 2‐boraindane compound. The mechanism of the former reaction has been computationally elucidated, and the differences between this route and the pathway to 1‐boraindanes is discussed. These reactions further the understanding of the chemistry of the increasingly popular mono‐base adducts of diborane(4), demonstrate the versatility of isonitriles in comparison to standard two‐electron donors, and elucidate selective routes to boron‐containing polycyclics, such as those being proposed as analogues for conventional organic pharmaceuticals. Abstract : Breaking bonds, making rings : The reactions of isonitriles with diborane(4) compounds are shown to provide routes to polycyclic boraindane species (see scheme). The regiochemistries of the final boraindanes are shown to be dictated by the regiochemistries of the starting materials.